Christian radio: the growth of a mainstream broadcasting force - Lochte, Robert H. (McFarland, 2006)
"This book examines the progression of Christian radio from its beginnings on tiny local stations to its presence on network and satellite radio of today. The author notes the factors that brought Christian music into the mainstream and discusses how network policies and regulations affected the development of Christian radio"--Provided by publisher